Perilaku Sosial Anak 5-6 Tahun dalam Kegiatan Sentra Bermain Peran di TK Labschool Jakarta - Yuliani Eka Putri; Nurbiana Dhieni; Hapidin Hapidin (Indonesian Journal of Educational Counseling, 2020)
SOCIAL BEHAVIOR OF CHILDREN AGED 5-6 YEARS IN ROLE PLAYING CENTER ACTIVITIES AT TK LABSCHOOL JAKARTA. This study aims to find and build theories of the forms of social behavior of children 5-6 years in the role playing center activities, the process of the formation of social behavior of children 5-6 years in the role playing center activities, the role of the teacher in the formation of social behavior of children 5-6 years in the role playing center activities, as well as the role of parents in shaping the social behavior of children 5-6 years in the role playing center activities. This research uses a qualitative approach with a case study method. The results of the study found that the social behavior of children 5-6 years old in Labschool Kindergarten Jakarta showed social behavior related to human relations, namely good human relations (social humanity), namely empathy, tolerance, cooperation, responsibility, fair, close behavior , share and wait their turn.